2020
DOI: 10.1080/09243453.2020.1764593
|View full text |Cite
|
Sign up to set email alerts
|

Teacher and school determinants of teacher job satisfaction: a multilevel analysis

Abstract: Teacher job satisfaction is an essential factor for teachers' and school effectiveness and students' academic and educational achievement. The present research aims to identify variables that contribute to job satisfaction in a Portuguese sample of lower secondary education teachers, using data from the Teaching and Learning International Survey (TALIS) 2013. Two questionnaires were used to collect data: a school principal's questionnaire, and a teacher questionnaire. Hierarchical linear modelling was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(75 citation statements)
references
References 69 publications
5
63
0
7
Order By: Relevance
“…In the studies carried out by Celik (2010), Gencturk (2008), Green, Machin, Murphy, and Zhu (2008), (Lopes and Oliveira, 2020), Ocal (2011) and Yılmaz (2012), it was revealed that teachers working in private schools have higher JS because all kinds of opportunities in private schools are higher than in public schools, wages are more satisfactory, physical-technological infrastructure is sufficient, education and selfdevelopment activities are given more, working conditions are better, and the number of students in the classes is lower. These results support the results of the meta-analysis study.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the studies carried out by Celik (2010), Gencturk (2008), Green, Machin, Murphy, and Zhu (2008), (Lopes and Oliveira, 2020), Ocal (2011) and Yılmaz (2012), it was revealed that teachers working in private schools have higher JS because all kinds of opportunities in private schools are higher than in public schools, wages are more satisfactory, physical-technological infrastructure is sufficient, education and selfdevelopment activities are given more, working conditions are better, and the number of students in the classes is lower. These results support the results of the meta-analysis study.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…This difference may reflect the greater autonomy of private schools. For instance, private schools can select their students and teachers, and they can set their culture and disciplinary regulations (Lopes & Oliveira, 2020).…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…In the studies carried out by Celik (2010), Gencturk (2008), Green, Machin, Murphy, and Zhu (2008), (Lopes andOliveira, 2020), Ocal (2011) and Yılmaz (2012), it was revealed that teachers working in private schools have higher JS because all kinds of opportunities in private schools are higher than in public schools, wages are more satisfactory, physical-technological infrastructure is sufficient, education and selfdevelopment activities are given more, working conditions are better, and the number of students in the classes is lower. These results support the results of the meta-analysis study.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…JS for teachers can be stated as teacher's attitude towards his/her students and school (Vural, 2004;Zembylas & Papanastasiou, 2004). Teacher JS is an essential factor for teachers' and school effectiveness and students' academic and educational achievement (Lopes & Oliveira, 2020). JS level of teachers isaffected by personal characteristics, such as age, gender, and educational level as well as many organizational factors, such as salary, the perspective of administrators, school type (private/public), working conditions, and social relationships (Vural, 2004;Yaramıs & Cinkir, 2014).…”
Section: Job Satisfaction: Private and Public Schoolsmentioning
confidence: 99%
“…Teachers as the main human assets of the educational system are no exception in this regard. According to Lopes and Oliviera (2020), teacher job satisfaction is a determiner of the effectiveness of not only the teacher him/herself but also that of the students, the school environment and the educational system at large. The repercussion of teachers' job dissatisfaction could be the heavy costs of selection, training and recruiting new teachers.…”
Section: Introductionmentioning
confidence: 99%